Sikkerhetspolitikk og militærmakt i Arktis - Wegge, Njord (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2023)
Security Policy and Military Strength in the Arctic presents new Norwegian research in High North defence and security policy topics. Against the backdrop of today's security situation, the book provides a unique introduction to the role military strength plays in the region. The book will be of interest to all those concerned with defence policy issues. Through research contributions by experts in land, sea and air power conditions, Security Policy and Military Strength in the Arctic renders a comprehensive overview that will be especially relevant for students at the Norwegian military academies and others studying political science and history, as well as researchers and practitioners in the field. An additional objective of the book is to advance the debate on the role of the military in the northern regions and the Arctic, and contribute to increasing awareness of ongoing developments in defence and security policy in the North.